Onde a luta se travar: a expansão das Assembleias de Deus no Brasil urbano (1946-1980) - Fajardo, Maxwell Pinheiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Assembly of God Church is Brazil's second largest religious group according to the latest Demographic Census. Founded in Belem in 1911, its expansion took place in line with a number of social changes in Brazil during the twentieth century. Among such changes, are highlighted the complementary processes of industrialization and urbanization of the country, evident especially from the second half of the century. It was from this period that the Assemblies of God and other Pentecostal denominations of orientation began to draw attention in the Brazilian religious field. Since 1960 academic studies point to the Pentecostal churches benefited the masses of migrants who came to the cities to provide the manpower for expanding industries, concluding there is a direct link between urbanization and the Pentecostal growth. However, although inserted in the same context, not all denominations have the same growth rate. The Assemblies of God, for example, now have six times more members than the second largest Pentecostal church, also centenary Christian Congregation of Brazil, is having the advantage to have been born around the city. Thus, we start from the assumption that the church member growth in the urban world must be understood not only in the light of external social, but also from the internal dynamics of the Church organization. One of the preponderant factors in this item is a sui generis way Assemblies of God were able to combine their different internal divisions around the same denominational platform without it represented the disintegration or the disintegration of the Church in an institutional fraying process unobservable in any other Brazilian Pentecostal church. Moreover, we also took into account their own cultural codes of the name, born in the overlapping of the Swedish experience of its early leaders, the migratory experience of its members and their own responses developed...

A Igreja Assembleia de Deus é o segundo maior grupo religioso do Brasil de acordo com os últimos Censos demográficos. Fundada em Belém do Pará em 1911, sua expansão se deu em consonância com diversas transformações sociais ocorridas no Brasil durante o século XX. Dentre tais transformações, ganham destaque os processos complementares de industrialização e urbanização do país, em evidência de modo especial a partir da segunda metade do século. Foi a partir deste período que as Assembleias de Deus bem como as demais denominações de orientação pentecostal começaram a chamar a atenção no campo religioso brasileiro. Desde a década de 60 estudos acadêmicos apontam como as igrejas pentecostais beneficiaram-se das massas de migrantes que chegavam às metrópoles para fornecerem a mão-de-obra para as indústrias em expansão, concluindo existir uma ligação direta entre a urbanização e o crescimento pentecostal. No entanto, embora inseridas no mesmo contexto, nem todas as denominações tiveram o mesmo ritmo de crescimento. As Assembleias de Deus, por exemplo, hoje contam com seis vezes mais membros que a segunda maior igreja pentecostal, a também centenária Congregação Cristã no Brasil, esta tendo a vantagem de já ter nascido no espaço urbano. Desta forma, partimos da hipótese de que o crescimento assembleiano no mundo urbano deve ser entendido não apenas à luz das transformações sociais externas, mas também a partir da dinâmica interna de organização da Igreja. Um dos fatores preponderantes neste item é a forma sui generis como as Assembleias de Deus conseguiram agregar suas diferentes cisões internas em torno de uma mesma plataforma denominacional sem que isto representasse a desestruturação ou o esfacelamento da Igreja, em um processo de esgarçamento institucional não observável em qualquer outra igreja pentecostal brasileira. Além disso, também...
Keywords: Igrejas pentecostais; Igrejas urbanas; Urbanização; Industrialização; Pentecostal churches